Conflict Coaching in Complex Adaptive Healthcare Systems: Conflict Resolution or Transformation? - Benjamin Freedman
Coaching has emerged as an important development activity in the clinical education landscape. Simultaneously, dispute resolution practitioners have embraced 'conflict coaching', a one-to-one conflict problem solving process aimed at enhancing the coachee's conflict management capability. This paper examines the differences between popular conflict coaching models and considers their application in the clinical skills development environment within complex adaptive healthcare systems. The ontology and epistemology of five conflict coaching methods are compared to highlight the influence of solutions-focussed and transformative traditions. A case study on the application of coaching in a complex healthcare system (using patient flow between an Emergency Department and an Intensive Care Unit), demonstrates the importance of adopting a coaching technique which is translatable to the coachee's practice environment. Implications for practice and opportunities for further development of transformative conflict coaching methods for complex healthcare environments are discussed.